The perspective of using MOOCs in journalism education: Case study of mobile journalism MOOC users’ experiences - Kovačević, Petra; Perišin, Tena (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2017)
Through analysing massive open online courses (MOOC) participants’ experiences and perceptions of a 20-week course in mobile journalism, this paper examines the potential obstacles, challenges and opportunities in providing education in this specific field. Results confirm the problematic low retention rate for MOOCs and show that this type of course demands more effort from participants by asking them to complete practical assignments away from the comfort of their homes. The content of the course, as well as quality communication with tutors is key for motivation and progress of participants in this MOOC. Consideration of technical resources for this type of remote training (smartphones and other equipment) is recommended, along with more interactive sessions that enhance the learning experience by connecting closer not only participants with tutors but participants with each other.